DESIGN, SYNTHESIS, AND EVALUATION OF NOVEL TYROSINASE INHIBITORS FOR SKIN DEPIGMENTATION - SALMAN, AMANI Y.; NAJDAWI, MANAL M.; AL-SHA’ER, MAHMOUD A.; AL JBOUR, NAWZAT D.; DAGHMASH, RAWAND M.; HASSOUNEH, LOAY K.; ABUDAYEH, ZEAD H.; SIRHAN, ALA’ Y.; AL-AKEEDI, MOHAMMED (International Journal of Applied Pharmaceutics, 2026)
Objective: Hyperpigmentation is a prevalent dermatological condition caused by excessive melanin production, primarily catalyzed by the enzyme tyrosinase. Existing depigmenting agents, such as hydroquinone and kojic acid, are limited by cytotoxicity, instability, and suboptimal efficacy. This study aimed to design, synthesize, and evaluate structurally novel tyrosinase inhibitors derived from cinnamic acid to overcome these limitations. Methods: Tencinnamic acid-based derivatives were designed with strategic modifications, including esterification with hydroquinone and aromatic moieties, to enhance binding affinity and stability. Molecular docking studies were conducted using tyrosinase crystal structures (PDB IDs: 3NQ1 and 5I38) to identify key binding interactions. Six lead compounds were synthesized and structurally characterized via NMR and FTIR spectroscopy. Their tyrosinase inhibitory activity was assessed in vitro using mushroom tyrosinase under standardized assay conditions. Results: Molecular docking revealed favorable interactions within the tyrosinase active site, with compound 9 exhibiting the highest docking scores. In vitro assays confirmed compound 9 as the most potent inhibitor, with an IC₅₀ value of 31.35 µg/ml, outperforming kojic acid (IC₅₀ = 94.96 µg/ml) and hydroquinone (IC₅₀ = 772.8 µg/ml) under identical conditions. Conclusion: Compound 9 demonstrated superior tyrosinase inhibition compared to conventional agents, indicating its potential as a safer and more effective alternative for treating hyperpigmentation. These findings support further development of compound 9 for use in topical formulations targeting melasma and related pigmentary disorders, with planned follow-up studies including in vivo efficacy and safety evaluations.